2007
DOI: 10.1592/phco.27.10.1425
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant Hypersensitivity Syndrome: Implications for Pharmaceutical Care

Abstract: Anticonvulsant hypersensitivity syndrome (AHS) is a delayed adverse drug reaction associated with the use of aromatic anticonvulsant drugs. It has been most commonly reported with the use of phenytoin, carbamazepine, and phenobarbital. Although its occurrence is rare, 1 in every 1000-10,000 exposures, AHS is a serious adverse event often resulting in hospitalization and even death. The clinical manifestations of AHS include a triad of symptoms consisting of dermatologic rashes, fever, and evidence of systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 44 publications
(87 reference statements)
0
60
1
9
Order By: Relevance
“…The toxic intermediaries in the metabolism of anticonvulsant drugs, arene oxides, can accumulate and directly bind to macromolecules, causing subsequent cell death as well as acting as prohaptens that bind to T cells, initiating a T-cell immune response and systemic reactions (12).…”
Section: Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…The toxic intermediaries in the metabolism of anticonvulsant drugs, arene oxides, can accumulate and directly bind to macromolecules, causing subsequent cell death as well as acting as prohaptens that bind to T cells, initiating a T-cell immune response and systemic reactions (12).…”
Section: Pathogenesismentioning
confidence: 99%
“…Drug eruption occurs in approximately 90-100% (3,10,12,(33)(34)(35)(36) of patients with AHS and can range from an exanthematous eruption to more serious reactions like SJS or TEN (9). Desquamation occurs with resolution (8).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Because cross-reactivity can be as high as 75%, they recommended that physicians be taught not to use these agents in such situations, but to instead use VPA, benzodiazepine, lamotrigine, and gabapentin. 8,9 Alldredge et al 10 reported that before the onset of symptoms, physicians for 3 of 4 patients with acute hypersensitivity syndrome (AHS) switched their medications to an anticonvulsant with an aromatic ring in the structure. They also reported that the symptoms subsided after the interruption of the medication and that all patients recovered.…”
Section: Introductionmentioning
confidence: 99%